Computational Toxicology: Endocrine Disrupting Effects of Lavender and Tea Tree Metabolites - Selvira Anandia Intan Maulidya; Baiq Risky Wahyu Lisnasari; Indra Purnomo; Tuhfatul Ulya; Wayan Cintya Ganes Budastra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
While Lavandula angustifolia (lavender) and Melaleuca alternifolia (tea tree) are widely utilized in diverse products for their rich bioactive secondary metabolites, emerging evidence now fules concerns about their potential endocrine-disrupting activities. This study aimed to investigate the endocrine-disrupting potential of selected secondary metabolites from lavender and tea tree via an in silico molecular docking approach. Molecular interactions were evaluated against 18 human endrocine receptors using Endocrine Disruptome in silico tools and binding affinities were analyzed to assess potential toxicity. Docking analysis revealed that all lavender anda tea tree secondary metabolites have the potential to interact as androgen receptor antagonists, exhibiting minor, medium, and high probabilities of such activity. Additionally, more than 20% of lavender secondary metabolites and 10% of tea tree secondary metabolites are predicted to be capable of binding to the mineralocorticoid receptor, as well as thyroid receptors alpha and beta. These findings suggest a plausible mechanism by which these phytochemicals could exert endocrine-disruptor effects. In conclusion, the study provides preliminary computational evidence supporting the hypothesis that certain lavender and tea tree sceondary metabolites may act as endocrine-disrupting agents. Further in vitro and in vivo studies are warranted to assess their toxicological implications for long-term human exposure.